Autoeficácia e motivação acadêmica: um estudo sobre a permanência acadêmica nos cursos técnicos de educação a distância do instituto metrópole digital, câmpus mossoró - Lima, Carmem Tassiany Alves de (Universidade Federal Rural do Semi-Árido, 2018)
Nowadays, the search for technical courses has significantly increased. Therefore, Distance Education Courses (DE) contribute to this growing vocational professional traning.The Digital Metropolis Institute, in Rio Grande do Norte , offers technical courses in the area of information technology, available through semi-presential Distance Education Courses (ED) modality, composing multiprofessional team of student assistance in the work against evasion. However, social issues have little effect or minimal interference in student evasion, since those issues are under academic autonomy. The incoming student in (DE) needs to develop the necessary skills for this teaching-learning methodology. Therefore, self-efficacy, in which it designates the individual's belief in his or her ability to perform a given task is the main point of this work. Since, the greater the belief in academic self-efficacy, the better student expectancy is expected and, consequently, a positive impact on the student's permanence.This study aims to illustrate and to analyze the relationship between academic self-efficacy and student permanence , as well as the relationship between social, historical-educational and motivational arrangement and student’s academic self-efficacy. Methodologically, this is a quantitative and qualitative research, that took place at The Digital Metropolis Institute (IMD), campus UFERSA Mossoró/RN, which analyses data from 53 regular students and 16 schood drop-outs from the basic level 2017.1. It was used as instruments , the Socioeconomic Questionnaire for IMD Social Service, the Motivation Scale for Learning, the Self-efficacy Scale in Higher Education adapted to the reality of the technical courses of intermediate level developed throughout the work and a structured interview script. As a result, statistical tests showed significant difference between the first week academic self-efficacy and the the last month of classes, among regular students. It was clear the decrease of self-efficacy, what shows huge efforts from the students in order to reach the required ability to do a Distance Education student Courses. Those students began to consider their beliefs in their own self-efficacy in a better way. Among social and historical-educational compositions, only the variable of "educational level" showed significant difference by the last month of classes, in which higher education people tend to be more self-confident about academic autonomy . Regarding academic motivation, there was no significant difference among the average reported. The quantitative analysis showed that regular or permanent students developed the ability to manage the effort and time required to study in virtual environment (AVA), as well as motivation to reach professional success This scenario is different among drop-out students or evaded students , in whom the statistical tests with self-efficacy and academic motivation, as well as in the qualitative analysis, presented absence of integration behavior with the virtual environment (AVA) and low motivation .Under technical courses learning model it is clear the need for multiprofessional team to assist students, improve pedagogical actions towards teachers and tutors, in order to engage students through practical experience, persuasion, as well as academic motivation. It is important to provide emotional support and familiar, and to develop studies mothods and technological support to the students, in order to minimize bad experiences and improve student retention among potential school drop-outs
Keywords: Autoeficácia acadêmica; estudante; permanência acadêmica; Academic self-efficacy; student; student permanence; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES